Wilms' tumour: A review of 15 years recent experience - Laura Illade; Carmen Hernandez-Marques; Maria Cormenzana; Alvaro Lassaletta; Maitane Andión Catalán; David Ruano; Victoria Fioravantti; Luis Madero López (Elsevier, 2018)
Introduction: Wilms' tumour is the most frequent renal tumour in children. Multi-modal treatment includes chemotherapy and surgery, with or without radiotherapy. The survival is excellent, with rates exceeding 90%. A review is presented on our experience over the last 15 years of treating Wilms' tumour in Hospital Niño Jesús, Madrid. Patients and methods: A retrospective study was conducted on 40 consecutive paediatric patients diagnosed with nephroblastoma between 2002 and 2016 in the Hospital Niño Jesús in Madrid. The clinical characteristics, diagnostic methods, treatment, and follow-up were analysed. Results: Of the 40 patients, 23 were boys, with a median age at diagnosis of 2.5 years (range, 4 months-15 years). Three patients underwent initial nephrectomy, three received a fine needle aspiration biopsy, followed by chemotherapy, and 34 patients started pre-operative chemotherapy directly. The median follow-up of the patients was 6.75 years (range, 10 months-13.92 years).Two patients died from disease progression. There were no treatment-related deaths. Overall survival and event-free survival at 5 years was 94.6 ± 3.7% and 89.4 ± 5%, respectively. Conclusion: Wilms' tumour treatment is a success of modern medicine, currently achieving a survival rate of 95% in our series. Resumen: Introducción: El tumor de Wilms es el tumor renal más frecuente en la edad pediátrica. Su tratamiento es multimodal: incluye quimioterapia y cirugía, con o sin radioterapia. La supervivencia de estos pacientes es excelente, superando el 90%. Presentamos la experiencia de nuestro centro en el tratamiento del tumor de Wilms durante los últimos 15 años. Pacientes y métodos: Se ha realizado un estudio retrospectivo de 40 pacientes pediátricos diagnosticados de forma consecutiva de nefroblastoma entre 2002 y 2016 en el Servicio de Hemato-Oncología pediátrica del Hospital Niño Jesús de Madrid. Se analizaron las características clínicas, los métodos diagnósticos, el tratamiento realizado y la evolución posterior. Resultados: De los 40 pacientes, 23 eran niños con una mediana de edad al diagnóstico de 2,5 años (rango, 4 meses-15 años). A 3 pacientes se les realizó nefrectomía inicial, 3 recibieron una punción aspiración con agua fina, seguida de quimioterapia y 34 pacientes recibieron quimioterapia preoperatoria directamente. La mediana de seguimiento de los pacientes fue de 6,75 años (rango, 10 meses-13,92 años).Dos pacientes fallecieron de progresión de su enfermedad. Ningún paciente falleció de toxicidad en relación con el tratamiento. La supervivencia global y la supervivencia libre de evento a los 5 años fue del 94,6 ± 3,7% y 89,4 ± 5%, respectivamente. Conclusión: El tratamiento del tumor de Wilms es un éxito de la medicina moderna, consiguiendo en la actualidad una supervivencia que en nuestra serie alcanza el 95%.